Physical Activity and Nutrition Survey and Evaluation for Public Health - Pippi, Roberto; Fanelli, Carmine Giuseppe; Vandoni, Matteo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Physical activity and nutrition are two of the most important modifiable lifestyle factors affecting health status, both in healthy people and in special populations with metabolic disorders and non-communicable diseases (e.g., obesity and type 2 diabetes (DM2)). Moreover, assessing these aspects is mandatory to implement healthy lifestyle habits and modifications properly. The aim of this Special Issue is to expand the knowledge regarding physical activity and human nutrition, with an emphasis on the assessment and evaluation of public health, in healthy people, athletes, and both general and pathological populations, during the entire lifespan. We also present some papers that focus on the importance of evaluation through surveys, tests, or other forms of evaluation in different settings (i.e., sport and clinical practice) to better orient interventions for public health improvement.